(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the author specifies, that during the war operations and occupation higher educational institutions of Ukraine suffered huge material and personnel losses. The restoration of higher education system started right after the liberation of the Ukrainian lands. Despite the difficult post-war social and economic conditions, the limited opportunities of financing, already in the end 1943 some high schools started working as early as 1943 and up to the end 1945 the pre-war system of higher education practically has been completely restored.